Phase Solubility Studies Of Metformin Inclusion Complexes With Various Polymers Of Β-Cyclodextrin And Its Derivatives (Journal of Pharmaceutical Negative Results, 2023)
With the help of inclusion complexes formed with β-cyclodextrin (β-CD), hydroxypropyl β-cyclodextrin (HP-β-CD), and randomly methylated β-cyclodextrin (RAMEB), respectively, the current study aims to assess the potential for improving the solubility of metformin (MET), an oral antidiabetic drug, in water. It also estimates their composition and apparent stability constants, Kst, from phase-solubility diagrams. We have observed that the phase solubility diagrams of MET - β-CD and RAMEB are B type, whereas the ones for the MET - HP-β-CD inclusion complex are A type. Since the zwitterionic structure of MET is lipophilic, all calculations were carried out in buffered phosphate solutions (pH 6). The phase-solubility diagrams show that the presence of β-CD and its derivatives, HP-β-CD and RAMEB, enhances the solubility of MET to varying degrees depending on the type of cyclodextrin.